Peranan Amil sebagai Pengelola Zakat untuk Kesejahteraan Umat di Kota Bima - Hamidy Thalib; M. Irwan; Ihsan Ro’is (Institut Agama Islam Negeri Madura, 2016)
This research aims to: 1) know how to manage your Amil way in Zakat Management in the Bima city, 2) know the role of Amil as Zakat manager in the people’s welfare in the Bima city. This research uses qualitative descriptive method with field research type (field research). The reseach results found that the Amil way manages zakat namely there is in accordance with the prophethood principle and is not in accordance with the prophethood principle. While his role as a manager for the people’s welfare is not yet maximum by looking at the utilization of Zakat funds. Where its utilization is more directed to consumptive nature while the productive nature is too few.